How effective are secondary sanctions? - Moon, Yechan (KDI School, 2022)
Are secondary economic sanctions effective? The United States (US) introduced secondary sanctions to complement sanctions from the United Nations (UN). This paper examines whether the US secondary sanctions are effective by examining the case of sanctions against North Korea by exploiting the variation in implementation of sanctions against North Korea based on the analysis of sanction implementation reports to the UN, and trade volume data at dyadic level for 203 countries between 2001 and 2020. The findings suggest that secondary sanctions are relatively ineffective, while UN sanctions are still a helpful tool. Such findings are robust to the inclusion or exclusion of China into the sample. The implications from the findings suggest that more efforts to convince others to participate in the implementation of the UN sanctions rather than pursuing unilateral secondary sanctions can be more effective in the part of the US.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: Economic sanctions, American--Korea (North); Nuclear nonproliferation--Korea (North)